Elective abortion: Clinical practice guidelines from the French College of Gynecologists and Obstetricians (CNGOF). (March 2018) - Vayssière, Christophe; Gaudineau, Adrien; Attali, Luisa; Bettahar, Karima; Eyraud, Sophie; Faucher, Philippe; Fournet, Patrick; Hassoun, Danielle; Hatchuel, Marie; Jamin, Christian; Letombe, Brigitte; Linet, Teddy; et al.
Abstract: The number of elective abortions has been stable for several decades. Many factors explain women's choice of abortion in cases of unplanned pregnancies. Early initiation of contraceptive use and a choice of contraceptive choices appropriate to the woman's life are associated with lower rates of unplanned pregnancies. Reversible long-acting contraceptives should be favored as first-line methods for adolescents because of their effectiveness (grade C). Ultrasound scan before an elective abortion must be encouraged but should not be obligatory (professional consensus). As soon as the embryo appears on the ultrasound scan, the date of pregnancy is estimated by measuring the crown-rump length (CRL) or, from 11 weeks on, by measuring the biparietal diameter (BPD) (grade A). Because reliability of these parameters is ±5 days, the abortion may be done if measurements are respectively less than 90 mm for CRL and less than 30 mm for BPD (professional consensus). A medically induced abortion, performed with a dose of 200 mg mifepristone combined with misoprostol, is effective at any gestational age (Level of Evidence (LE) 1). Before 7 weeks, mifepristone should be followed 24–48 h later by misoprostol, administered orally, buccally, sublingually, or even vaginally followed if needed by a further dose of 400 μg after 3 h, to be renewed if needed after 3 h (LE 1, grade A). After 7 weeks, administration of misoprostol by the vaginal, sublingual, or buccal routes is more effective and better tolerated than by the oral route (LE 1). Cervical preparation is recommended for systematic use in surgical abortions (professional consensus). Misoprostol is a first-line agent for cervical preparation at a dose of 400 μg (grade A). Vacuum aspiration is preferable to curettage (grade B). A uterus perforated during surgical aspiration should not routinely be considered to be scarred (professional consensus). An elective abortion is not associated with a higher risk of subsequent infertility or ectopic pregnancy (LE 2). The medical consultation before an elective abortion generally does not affect the decision to end or continue the pregnancy, and most women are sufficiently certain about their choice at this time. Women appear to find the method used most acceptable and to be most satisfied when they were able to choose the method (grade B). Elective abortions are not associated with an increased rate of psychiatric disorders (LE 2). However, women with psychiatric histories are at a higher risk of psychological disorders after the occurrence of an unplanned pregnancy than women with such a history (LE 2). For surgical abortions, combined hormonal contraceptives — oral or transdermal — should be started on the day of the abortion, while the vaginal ring should be inserted 5 days afterwards (grade B). For medical abortions, the vaginal ring should be inserted in the week after mifepristone administration, while the combined contraceptives should begin the same day as the misoprostol or the day after (grade C). Contraceptive implants should be inserted on the same day as a surgical abortion, and may be inserted the day the mifepristone is administered for medical abortions (grade B and C respectively). In case of medical abortion, the implant can be inserted the same day the mifepristone is administered (grade C). Both the copper IUDs and levonorgestrel intrauterine system should be inserted on the day of the surgical abortion (grade A). After medical abortions, an IUD can be inserted in 10 days after mifepristone administration, after ultrasound scan verification of the absence of an intrauterine pregnancy (grade C).